Economics as a science - Boulding, Kenneth E. (New York : McGraw-Hill Book, 1970)
The main purpose of these essays is to introduce those who already have some acquaintance with economics to what might be called the larger scientific background of the subject.
Includes bibliographical references.
ijb, 18/01/2019
Loans
Keywords: Economics